OS AGROECOLOGISTAS DE GUARAPUAVA – PR: PERSPECTIVAS E ACESSO ÀS POLÍTICAS QUE INCORPORAM A AGROECOLOGIA - Taques, Nilson Roberto (2014)
The aim of this study is to identify the agroecologists' perspectives, setbacks and accessibility to the public policies which incorporate the foment to the agroecology in Guarapuava Pr. The research is based on qualitative exploratory data using literature review, documental analysis, semi-structured interviews and content analysis. The spatial cut corresponds to the city of Guarapuava. The theoreticalconceptual framework was founded on the theory of Gramscian Inspirational State, which supports that the agroecologic public policies appear in the context of the reevaluation of the family farming which was established in the 90' in Brazil, in response to the rural social manifestations very active in that decade. These manifestations were counter-hegemonic and were able to open political opportunities in the State bureaucratic structure. Nevertheless, these agroecologists face hegemonic groups whose roots are linked to the national state formation and to the large landed estate, and even at the present time, count on solid political representativeness. The bourgeois agribusiness integrates the hegemonic model of modernization of the Brazilian society, whereas family farming in Brazil struggles to make an alternative project viable. The agroecology present in this project is regulated by the civil society, which is opposed to the bourgeois agribusiness, and seeks the support of the state intervention specially with the implementation of public policies that enable the establishment and development of this productive practice based on economical, social and environmental sustainability. In Guarapuava, the option for agroecology is weakened by the low degree of organicity of the agroecologic social movements, and moreover, to be inserted in a political context dominated by rural oligarchies which intervene in the relationship between the local public policies and the organizations related to agroecology.